Codesigning implementation strategies to improve evidence‐based stroke rehabilitation: A feasibility study - Elizabeth A. Lynch; Lemma N. Bulto; Maria West; Dominique A. Cadilhac; Fawn Cooper; Gillian Harvey (Health Expectations)
Abstract Introduction People with lived experience are rarely involved in implementation science research. This study was designed to assess the feasibility of codesigning and delivering implementation strategies with people with lived experience of stroke and health professionals to improve evidence‐based stroke rehabilitation. Methods We used Experience‐Based CoDesign to design and deliver strategies to implement Stroke Clinical Guideline recommendations at one Australian inpatient stroke rehabilitation unit. Workgroups were formed with health professionals and people with 6–12 months experience of living with stroke (survivors and carers). Feasibility of the codesign approach (focusing on acceptability, implementation fidelity, signal of promise) was evaluated using mixed methods, using data from interviews, observations and inpatient self‐reported outcomes. Results Of 18 people with stroke invited, eight (44%) agreed to join the lived experience workgroup. All disciplines with ≥1 full‐time staff members on the stroke unit were represented on the health professional workgroup. Median workgroup attendance over 6 months was n = 8 health professionals, n = 4 survivors of stroke and n = 1 carers. Workgroup members agreed to focus on two Guideline recommendations: information provision and amount of therapy. Workgroup members indicated that the codesign approach was enjoyable and facilitated effective partnerships between health professionals and lived experience workgroup members. Both cohorts reported contributing valuable input to all stages of the project, with responsibility shifting between groups at different project stages. The codesigned strategies signalled promise for improving aspects of information provision and creating additional opportunities for therapy. We could not compare patient‐reported outcomes before and after the implementation period due to high variability between the preimplementation and postimplementation patient cohorts. Conclusion It is feasible to codesign implementation strategies in inpatient rehabilitation with people with lived experience of stroke and health professionals. More research is required to determine the effect of the codesigned strategies on patient and service outcomes. Patient or Public Contribution People with lived experience of stroke codesigned and evaluated implementation strategies. Author F. C. has lived experience of stroke and being an inpatient at the inpatient rehabilitation service, and has provided input into analysis of the findings and preparation of this manuscript.